Selected Epidemiological Aspects of Schizophrenia: A Cross Sectional Study at Tertiary Care Hospital in Maharashtra - Ashturkar, Madhura D; Dixit, Jaggnath V (National Journal of Community Medicine, 2013)
Background: To study epidemiological factors in cases of schizophrenia, as schizophrenia begins in early age of life and treatment includes pharmacological and psychosocial interventions and rehabilitation of patients. Objectives: To study agent, host and environmental factors, to study clinical profile and identify, familial, psycho – social factors Methods: Diagnosed cases of schizophrenia according to WHO ICD -10 classification at tertiary care hospital in central Maharashtra between 1st Jan 2006 to 31st Dec 2006. The data was collected with pre-tested questionnaire by direct interview method. Socio- demographic variables were reported using descriptive statistics and age of onset of first symptom of schizophrenia were compared across gender by Chi- square test. Results: There were 48 men and 24 women with mean age of 30.26 years. 44.44% were unmarried, 50% were unemployed and 41.66% were in socio-economic class IV. Substance abuse and alcohol was found to be 83.33% among males. Age of onset of symptoms of schizophrenia found at earlier age in males than in females. Conclusion: Age of onset of first symptom were at earlier age in males than in females, this difference is found to be statistically significant.